Pengaruh Terapi Progressive Muscle Relaxation (PMR) terhadap Tingkat Stres Perawat yang Bertugas di Ruang Covid-19 Rumah Sakit Badan Pengusahaan Batam - Mira Agusthia; Saida Marlina Tambun; Rachmawaty M. Noer; Triyana Harlina Putri (Universitas Malahayati Lampung, 2022)
ABSTRACT High levels of work stress affect the performance, satisfaction, productivity, and caring behavior of nurses. The higher the work stress, the lower the nurse's performance, satisfaction, productivity, and caring behavior. Decreasing performance of nurses and the tendency to leave work because of fatigue, can cause an increase in the workload of sedentary nurses. This study was to see whether the effect of Progressive Muscle Relaxation (PMR) Therapy on the Stress Level of Nurses Serving in the Covid-19 Room in Batam Concession Agency Hospital in 2020.The experimental research design used was true experimental design with the approach of one group pre test and post test without control. The independent variable of Progressive Muscle Relaxation Therapy (PMR) is the dependent variable of the nurse's stress level. The population in this study were all nurses who served in the Covid-19 room at BP Batam Hospital. The analysis in this study is univariate and bivariate analysis and data processing using the marginal homogeneity test (p 0.05). The results showed that more than half (85%) of respondents before being given progressive muscle relaxation therapy were moderate stress. The results showed that more than half (90%) of respondents after being given progressive muscle relaxation therapy were mild stressors. The results of the analysis using the marginal homogeneity test of the pre-test and post-test stress levels showed a p value 0.005. This shows that there is an effect of Progressive Muscle Relaxation (PMR) with the stress level of nurses, so Ho is rejected and Ha is accepted, so it can be concluded that there is a significant influence between Progressive Muscle Relaxation (PMR) Therapy on the Stress Level of Nurses Serving in the Covid-19 Hospital Room. Batam Concession Agency in 2020. Keywords : Progressive Muscle Relaxation, Stress Level of Nurse ABSTRAK Tingkat stres kerja yang tinggi berpengaruh terhadap kinerja, kepuasan, produktivitas, dan perilaku caring perawat. Semakin tinggi stres kerja maka kinerja, kepuasan, produktivitas, dan perilaku caring perawat akan semakin rendah. Penurunan kinerja perawat dan adanya kecenderungan untuk meninggalkan pekerjaan karena lelah, dapat menyebabkan bertambahnya beban kerja pada perawat yang menetap. Untuk melihat adakah Pengaruh Terapi Progressive Muscle Relaxation (PMR) Terhadap Tingkat Stres Perawat Yang Bertugas Di Ruang Covid-19 Rumah Sakit Badan Pengusahaan Batam Tahun 2020. Desain Penelitian eksperimental yang digunakan adalah true eksperimental design dengan pendekatan one group pre test dan post test without control. Variabel independen Terapi Progressive Muscle Relaxation (PMR) variabel dependen tingkat stress perawat. Populasi pada penelitian ini adalah semua perawat yang bertugas di ruang Covid-19 Rumah Sakit BP Batam. Analisa pada penelitian ini yaitu analisa univariat dan bivariat dan pengolahan data menggunakan uji marginal homogenity (p 0,05). Lebih dari separuh (85%) responden sebelum diberikan terapi progressive muscle relaxation adalah stres sedang. Hasil penelitian menunjukkan lebih dari separuh (90%) responden setelah diberikan terapi progressive muscle relaxation adalah stres ringan. Hasil analisa dengan menggunakan uji marginal homogenity analisis pre test dan post test tingkat stress menunjukkan nilai p 0,005. Hal ini menunjukkan terdapat pengaruh Progressive Muscle Relaxation (PMR) dengan tingkat stress perawat demikian Ho ditolak dan Ha diterima sehingga dapat disimpulkan bahwa terdapat pengaruh yang signifikan antara Terapi Progressive Muscle Relaxation (PMR) Terhadap Tingkat Stres Perawat Yang Bertugas Di Ruang Covid-19 Rumah Sakit Badan Pengusahaan Batam Tahun 2020. Kata kunci: Relaksasi Otot Progressive, Tingkat Stres